The Phytochemical Bergenin Enhances T Helper 1 Responses and Anti-Mycobacterial Immunity by Activating the MAP Kinase Pathway in Macrophages - Dwivedi, Ved P.; Bhattacharya, Debapriya; Yadav, Vinod; Singh, Dhiraj K.; Kumar, Santosh; Singh, Mona; Ojha, Durbadal; Ranganathan, Anand; Van Kaer, Luc; Chattopadhyay, Debprasad; Das, Gobardhan (Frontiers in Cellular and Infection Microbiology, 2017)
Tuberculosis (TB) remains one of the greatest health concerns worldwide, which has hindered socio-economic development in certain parts of the world for many centuries. Although current TB therapy, “Directly Observed Treatment Short-course,” is effective, it is associated with unwanted side effects and the risk for the generation of drug-resistant organisms. The majority of infected individuals suc-cessfully confine the mycobacterial organisms and remain asymptotic unless immune responses are perturbed. Thus, host immunity can protect against TB and immunomodulation is therefore an attrac-tive therapeutic option. Previous studies have shown that TNF-α and Nitric Oxide (NO) in conjunc-tion with IFN-γ-producing T helper 1 (Th1) cells play critical roles in host protection against TB. Here, we show that bergenin, a phytochemical isolated from tender leaves of Shorea robusta, acti-vates the MAP kinase and ERK pathways and induces TNF-α, NO and IL-12 production in infected macrophages. We further show that bergenin induces Th1 immune responses and potently inhibits bacillary growth in a murine model of Mycobacterium tuberculosis infection. These findings identify bergenin as a potential adjunct to TB therapy.